2001
DOI: 10.1051/0004-6361:20010316
|View full text |Cite
|
Sign up to set email alerts
|

Mineral formation in stellar winds

Abstract: Abstract. S stars are transition objects at the top of the AGB between M-and C-stars. The third dredge-up in thermally pulsating AGB-stars transports freshly synthesised carbon from the He burning zone into the stellar atmosphere. If the carbon and oxygen abundance are about equal the star is classified as being of spectral type S. Stars at the top of the AGB are subject to large mass-loss caused by a strong stellar wind. At some distance from the star the temperature of the gas drops below the condensation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 46 publications
3
101
0
Order By: Relevance
“…In a stellar wind, however, the process of dust formation of the silicates does not run into completion until the gas has cooled below the stability limit of MgO and a significant fraction of the Mg is left over in the gas phase at this instant to form MgO. Our previous model calculations (Gail & Sedlmayr 1999;Ferrarotti & Gail 2001) have already shown that because of the nonequilibrium nature of condensation in stellar outflows a certain quantity of solid MgO should be formed. Since the MgO forms a solid solution with FeO it is more likely, however, that in the presence of Fe vapour in the gas phase magnesiowüstite Mg x Fe 1−x−δ is formed in the outflow and not pure MgO.…”
Section: Oxides Of Mg and Fementioning
confidence: 99%
See 3 more Smart Citations
“…In a stellar wind, however, the process of dust formation of the silicates does not run into completion until the gas has cooled below the stability limit of MgO and a significant fraction of the Mg is left over in the gas phase at this instant to form MgO. Our previous model calculations (Gail & Sedlmayr 1999;Ferrarotti & Gail 2001) have already shown that because of the nonequilibrium nature of condensation in stellar outflows a certain quantity of solid MgO should be formed. Since the MgO forms a solid solution with FeO it is more likely, however, that in the presence of Fe vapour in the gas phase magnesiowüstite Mg x Fe 1−x−δ is formed in the outflow and not pure MgO.…”
Section: Oxides Of Mg and Fementioning
confidence: 99%
“…The consumption of H 2 O, Fe, and Mg from the gas phase by formation of magnesiowüstite has to be considered analogous to Eqs. (51), (53), (54) of Ferrarotti & Gail (2001).…”
Section: Grain Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferrarotti & Gail (2006) performed extensive calculations of dust formation by low-and intermediate-mass stars during their AGB evolution for a wide range of initial stellar masses and metallicities, making these models the most suitable for use in evolutionary dust models. Their work is based on detailed theoretical models of non-equilibrium dust condensation in stellar winds, developed in a series of earlier papers (Gail & Sedlmayr 1987Ferrarotti & Gail 2001Gail 2003). These studies consider the formation of a multicomponent dust mixture in stationary, dust-driven winds with O-, C-, and S-chemistries.…”
Section: Dust Formation By Low-and Intermediate-mass Starsmentioning
confidence: 99%